Atypical Hemolytic Uremic Syndrome Post-Kidney Transplantation: Two Case Reports and Review of the Literature - Alasfar, Sami; Alachkar, Nada (Frontiers in Medicine, 2014)
Atypical hemolytic uremic syndrome (aHUS) is a rare disorder characterized by over-activation and dysregulation of the alternative complement pathway. Its estimated prevalence is 1-2 per million. The disease is characterized by thrombotic microangiopathy, which causes anemia, thrombocytopenia, and acute renal failure. aHUS has more severe course compared to typical (Infection-induced) HUS and is frequently characterized by relapses that leads to end stage renal disease (ESRD). For a long time, kidney transplantation for these patients was contraindicated because of high rate of recurrence and subsequent renal graft loss. The post-kidney transplantation recurrence rate largely depends on the pathogenetic mechanisms involved. However, over the past several years, advancements in the understanding and therapeutics of aHUS have allowed successful kidney transplantation in these patients. Eculizumab, which is a complement C5 antibody that inhibits complement factor 5a (C5a) and subsequent formation of the membrane attack complex, has been used in prevention and treatment of post-transplant aHUS recurrence. In this paper, we present two new cases of aHUS patients who underwent successful kidney transplantation in our center with the use of prophylactic and maintenance eculizumab therapy that have not been published before. The purpose of reporting these two cases is to emphasize the importance of using eculizumab as a prophylactic therapy to prevent aHUS recurrence post transplant in high-risk patients. We will also review the current understanding of the genetics of aHUS, the pathogenesis of its recurrence after kidney transplantation, and strategies for prevention and treatment of post-transplant aHUS recurrence.